2016
DOI: 10.1111/jzo.12361
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis of anti‐predator adaptation in a lizard with autotomizable blue tail against specific predators with different colour vision

Abstract: Juveniles of numerous lizard species have a vividly blue-coloured tail that likely serves to deflect predator attacks toward the autotomizable tail rather than the lizard's body. The shades of blue colour in the tails of juvenile Plestiodon latiscutatus lizards vary across populations, most notably among those island populations with different predator assemblages. Here, we determine if this intraspecific variation is associated with the differences in colour vision capabilities of lizard predator species. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…The majority of striped lizard species are strictly ground‐dwelling, and the angle at which the different predators (aerial vs. ground‐dwelling) typically view and attack lizards is therefore likely to differ. Furthermore, it has been shown that red tail colour attracts attacks by birds of prey such as raptors (Fresnillo et al ., 2015a), and blue tails appear to function against terrestrial predators such as snakes or ground‐dwelling birds (Cooper & Vitt, ; Brandley et al ., ; Kuriyama et al ., ). We therefore posit that different visual predators may impose selection favouring particular combinations of tail colour and the positioning of stripes in lizards.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of striped lizard species are strictly ground‐dwelling, and the angle at which the different predators (aerial vs. ground‐dwelling) typically view and attack lizards is therefore likely to differ. Furthermore, it has been shown that red tail colour attracts attacks by birds of prey such as raptors (Fresnillo et al ., 2015a), and blue tails appear to function against terrestrial predators such as snakes or ground‐dwelling birds (Cooper & Vitt, ; Brandley et al ., ; Kuriyama et al ., ). We therefore posit that different visual predators may impose selection favouring particular combinations of tail colour and the positioning of stripes in lizards.…”
Section: Discussionmentioning
confidence: 97%
“…Assuming that stripes have a redirective function, dorsal stripes are more likely to be used as signals to aerial predators such as birds, in contrast to lateral stripes which are more likely to be used against terrestrial predators such as snakes and mammals. These predator guilds may differ in their visual systems, and hence, the same tail colour may not be equally effective for attack deflection for both predator guilds (Kuriyama et al ., ). Therefore, we also explored whether (iv) the position of stripes on the body ( Lateral or Dorsal : Fig.…”
Section: Introductionmentioning
confidence: 97%
“…In ectotherms, incident radiation is converted into thermal energy primarily by integumental eumelanins 51 ; there is also a direct relationship between the density of these pigments and skin darkness 51 53 . In addition to melanins, non-endothermic vertebrate skins often contain a number of other biochromes, which together with finely organised nanostructures causing light interference, produce the variety of colour patterns seen in fish, amphibians and reptiles today 32 , 52 54 . However, contrary to recent claims 55 , non-melanic pigments and photonic nanosurfaces are not ubiquitous to all reptile skins.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit deflection offers to prey individuals and the costs of conspicuous patterning could therefore depend on the time of day; the deflective traits are likely adaptive to the time of day butterflies experience greater predation. Additionally, it has recently been reported that the shades of blue colour in the tails of juvenile Plestiodon latiscutatus lizards vary across island populations with different predator assemblages (Kuriyama et al 2016). Kuriyama et al (2016) found that tail colouration varied with the colour vision of specific predators.…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 98%
“…Additionally, it has recently been reported that the shades of blue colour in the tails of juvenile Plestiodon latiscutatus lizards vary across island populations with different predator assemblages (Kuriyama et al 2016). Kuriyama et al (2016) found that tail colouration varied with the colour vision of specific predators. Vivid blue reflectance occurred in communities with either weasel or snake predators (both groups of which can detect blue wavelengths), while UV reflectance was much higher in populations with only snake predators (snakes can detect UV, but weasels cannot).…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 98%